2020
DOI: 10.1002/acr.23855
|View full text |Cite
|
Sign up to set email alerts
|

Men and Women's Occupational Activities and the Risk of Developing Osteoarthritis of the Knee, Hip, or Hands: A Systematic Review and Recommendations for Future Research

Abstract: Objective To systematically review the evidence for an increased risk of osteoarthritis in the hip, knee, hand, wrist, finger, ankle, foot, shoulder, neck, and spine related to diverse occupational activities of men and women and to examine dose‐response information related to the frequency, intensity, and duration of work exposures and the risk of osteoarthritis (OA). Methods Established guidelines for systematic reviews in occupational health and safety studies were followed. MEDLINE, Embase, CINAHL, and Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 85 publications
(54 reference statements)
0
24
0
Order By: Relevance
“…A possible selection bias might exist as participants with jobs with the highest odds of knee OA were likely to be recruited and have their data reported. Compared to previous systematic reviews of occupations and knee OA , our study is the most comprehensive in including an increased number of relevant occupational exposures and sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible selection bias might exist as participants with jobs with the highest odds of knee OA were likely to be recruited and have their data reported. Compared to previous systematic reviews of occupations and knee OA , our study is the most comprehensive in including an increased number of relevant occupational exposures and sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanistic links between occupations and knee OA are believed to be biomechanical, with excessive knee forces generated during strenuous work tasks . Several studies have identified frequent workplace kneeling, squatting, and heavy lifting as risk factors for development and progression of knee OA . However, few studies have quantitatively synthesized the evidence , and no systematic review has compared the disease outcomes according to specific job titles.
Prevalence of knee osteoarthritis (OA) has been associated with work‐related repetitive joint movements and excess knee load, but little is known of the relationship between specific job titles and risk of knee OA, especially light‐to-moderate physically demanding occupations. Increased odds of knee OA were found in agriculture workers, construction workers, miners, service workers, houseworkers, and cleaners, who typically perform high levels of lifting, kneeling, climbing, squatting, and standing, compared to individuals with sedentary occupations. This evidence could help inform workplace regulators and insurers by identifying individuals who are frequently involved in specific work activities and may be susceptible to joint disorders; it could also help identify targeted industrial sectors that might need tailored prevention strategies for knee OA.
…”
Section: Introductionmentioning
confidence: 99%
“…Another review showed that cumulative physical workloads were associated with hip osteoarthritis in men; this review showed mixed evidence for physical demands and knee osteoarthritis, hip osteoarthritis and osteoarthritis in multiple other joints. 58 For high versus low OPA, there was an statistically significant increased risk of insomnia (OR 2.76, 95% CI 1.71 to 4.45), 61 with pooled results from four cross-sectional and three cohort studies, and high heterogeneity.…”
Section: Reviewmentioning
confidence: 97%
“…Although moderate physical activity is encouraged to improve one's general health, repetition or incorrect execution of movements is the prevailing cause of OA in both young and older adults ( 56 , 64 , 107 ). From a comprehensive review of recent studies, common occupational activities such as sitting (hip and knee OA), lifting (knee OA), driving (knee OA), and squat (lower limb OA) have been associated with increased risk of OA ( 108 , 109 ). These activities, if repeated, could be detrimental to the joint, as a study calculated the risk of developing localized OA to be twice as likely in individuals with occupations demanding repetitive physical activities compared to the average population ( 110 ).…”
Section: Applications Of Msc Therapies In Oamentioning
confidence: 99%